Šmolkovia 2. zv.: Babroš. Gargamelovo čarovné zrkadlo : (Les Schtroumpfs) - Culliford, Thierry, 1955-; Culliford, Pierre, 1928-1992; Jost, Alain, 1955- (Egmont, 2001)
Milí rodičia! Opäť k vašim deťom prichádzajú Šmolkovia s dvoma veselými príbehmi...